Q. 83.7( 41 Votes )

<span lang="EN-US

Answer :

2(x + 1) = 3(1-x)

Taking log base both sides

log(2(x + 1)) = log(3(1-x))

(x + 1) log 2 = (1 - x) log 3

x log 2 + x log 3 = log 3 - log 2

x(log 2 + log 3) = log 3 - log 2

x = (log 3 - log 2)/(log 2 + log 3)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

Write each of theAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics